1998
DOI: 10.1094/pdis.1998.82.7.830c
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Occurrence of Tomato Geminiviruses in Brazil, Associated with the New Biotype of the Whitefly Vector

Abstract: Although tomato golden mosaic virus (TGMV) was reported in Brazil more than 20 years ago (3), tomato-infecting geminiviruses have not been of economic significance in the country until recently. However, a sharp increase in the incidence of geminivirus-like symptoms in tomatoes has been reported in several areas of Brazil since 1994. This has coincided with the appearance of the B biotype of Bemisia tabaci, which, as opposed to the A biotype, readily colonizes solanaceous plants (2). We have isolated geminivir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
14

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 0 publications
0
32
0
14
Order By: Relevance
“…PCR analyses confirmed that these symptomatic plants were infected with begomoviruses, followed by many reports demonstrating the importance of these viruses [32]. Identification using partial genome sequence indicated high levels of diversity [7,9,23], which is expected after the spread of an efficient new vector.…”
Section: Discussionmentioning
confidence: 66%
“…PCR analyses confirmed that these symptomatic plants were infected with begomoviruses, followed by many reports demonstrating the importance of these viruses [32]. Identification using partial genome sequence indicated high levels of diversity [7,9,23], which is expected after the spread of an efficient new vector.…”
Section: Discussionmentioning
confidence: 66%
“…From the Northeast, the insect spread to other regions of the country where outbreaks were previously occasional and problems were caused largely due to its properties as a vector. Bean production was affected by the bean golden mosaic virus in many regions and tomato and soybean crops were also occasionally infected with geminiviruses transmitted by B. tabaci (Ribeiro et al, 1998;Ferreira et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…As espécies relatadas geralmente pertencem a Malvaceae, Euphorbiaceae e Fabaceae (Morales & Anderson, 2001). Alguns estudos demonstraram casos em que Begomovirus provenientes de plantas invasoras podem ser transmitidos para espécies cultivadas através do inseto-vetor ou mediante inoculação via extrato vegetal tamponado (Frischmuth et al, 1997;Faria et al, 2000;Morales & Anderson, 2001 (Faria & Maxwell, 1999;Ribeiro et al, 1998;Cotrim et al, 2004). Os resultados desses estudos revelam enorme variabilidade genética entre os isolados.…”
Section: Introductionunclassified